KEBERLANJUTAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH NON-PESANTREN - Elman, Moh. (CV. Jendela Gagasan, 2024)
This research aims to delve into the decline of students' interest and potential solutions to this phenomenon. The approach used in this research is qualitative with a case study literature type. The data sources include primary data sources such as students, teachers, and parents. Data collection techniques involve interviews and observations. The research results indicate that there is a decline in students' interest in learning Islamic education at school, caused by various internal and external factors. The solution to this decline in interest involves integrating a contextual approach through the development of the Islamic education curriculum, family support, and fostering additional skills to help students navigate future life challenges.